To find \(-24 \frac{4}{5} - 6 \frac{7}{10}\) using the additive inverse, you can rewrite the subtraction as adding the opposite (additive inverse) of the second number. So:
\[ -24 \frac{4}{5} - 6 \frac{7}{10} = -24 \frac{4}{5} + (-6 \frac{7}{10}) \]
Now, first, convert the mixed numbers into improper fractions:
-
Convert \(-24 \frac{4}{5}\): \[ -24 \frac{4}{5} = -\left(24 \times 5 + 4\right)/5 = -\left(120 + 4\right)/5 = -\frac{124}{5} \]
-
Convert \(-6 \frac{7}{10}\): \[ -6 \frac{7}{10} = -\left(6 \times 10 + 7\right)/10 = -\left(60 + 7\right)/10 = -\frac{67}{10} \]
Now we need to add \(-\frac{124}{5}\) and \(-\frac{67}{10}\). First, we need a common denominator. The least common denominator (LCD) of 5 and 10 is 10.
Convert \(-\frac{124}{5}\) to have a denominator of 10: \[ -\frac{124}{5} = -\frac{124 \times 2}{5 \times 2} = -\frac{248}{10} \]
Now we can perform the addition: \[ -\frac{248}{10} - \frac{67}{10} = -\frac{248 + 67}{10} = -\frac{315}{10} \]
Now simplify \(-\frac{315}{10}\): \[ -\frac{315 \div 5}{10 \div 5} = -\frac{63}{2} \]
Convert \(-\frac{63}{2}\) to a mixed number: \[ -31 \frac{1}{2} \]
Thus, the answer is:
\(-31 \frac{1}{2}\)